“3D·CoD”: A New Methodology for the Design of Virtual Reality-Mediated Experiences in Digital Archeology - Pujol-Tost, Laia (Frontiers in Digital Humanities, 2017)
Despite the capacity of virtual reality (VR) to recreate and enhance real and virtual worlds, many applications in Archeology aim at the photorealistic depiction of architectural spaces. On the other hand, little is known about their real communicational effectiveness. In this context, the EU-funded project {LEAP] proposed the concept of Cultural Presence as the theoretical and methodological foundation for a new kind of VR-mediated experience, and the UNESCO World Heritage Neolithic site of Çatalhöyük (Turkey) was chosen as case of application. During this process, a survey of design pipelines in Digital Archeology indicated that, to build such experiences, a new design and evaluation method may need to be adopted. This paper presents the process of building and testing “3D⋅CoD,” a new methodology for the design of VR-mediated experiences. Initially, different archeologists working at Çatalhöyük were engaged in a first workshop, aimed at establishing a specific instantiation of Cultural Presence and how to depict it by means of VR. To that end, observation, questionnaires, multimodal, and statistical analyses were used. The results of this field work were translated into a codesign hands-on methodology (“3D⋅CoD”), which was tested in a second workshop, with a different group of archeologists. In this case, observation and debriefing were used. The results of this evaluation suggest that codesign strategies are suitable for the creation of VR-mediated experiences, but that equally important is (1) to consider the codesigners’ concept of Archeology and (2) to think in terms, not of 3D models, but of Cultural Heritage goals and human experiences.